Socio-economic studies of scavengers in Malaysian landfills - Zahariman, A.H.; Mustafa, F.B.; Shahul Hamid, F. (2011)
Accelerating pace of urbanization has resulted with increasing generation of municipal solid waste (MSW). Approximately 90% of these wastes are sent to landfills without any material recovery process. As a result, it creates opportunity for scavenger to retrieve valuable materials from the waste stream. This is observed in most landfill in Malaysia where scavengers collect the recyclables as their source of income. This paper examines the socio-economic of scavengers and describes the management of scavenging activity in three landfill types namely Jeram Sanitary Landfill, Bukit Beruntung Open Dump and Dengkil non-sanitary Landfill, in Selangor, Malaysia. Jeram Sanitary Landfill and Dengkil non-sanitary Landfill were managed by Worldwide Holdings Pvt Ltd. while Bukit Beruntung Open Dump was managed by Hulu Selangor Municipal Council. The study is based on direct field observations and from the social survey among scavengers of the three landfills. Results indicate that, 71% of the active scavengers in the study area are foreigners, mostly Indonesians and they are full time scavengers. 85% of them choose to scavenge waste in landfill because they lack qualification for other job opportunities. On the other hand, 15% choose to be involved in scavenging activity because it generates higher income for them compared to other jobs. From the observations, the landfill management neither provide proper personal protective equipment (PPE) to the scavengers nor strictly enforce the usage of PPE despite the knowledge that PPE is a good method in reducing health risks among the scavenger. Also, the management in all types of landfill does not provide the necessary technical training for the scavengers. This resulted with the scavengers facing risks of health hazard due to their lack of knowledge and ignorance. Thus, the authorities should have better policies and legislations in landfill management in regards to the involvement of scavengers. It can be concluded that the presence of landfills with its ‘rich’ resources namely recyclables create the opportunity for the scavengers to improve their socio-economy. Yet, necessary precautions need to be taken by the authorities in order to prevent health risk to the scavengers.